Fast pole figure acquisition using area detectors at the DiffAbs beamline – Synchrotron SOLEIL. (1st December 2013) - Mocuta, Cristian; Richard, Marie‐Ingrid; Fouet, Julie; Stanescu, Stefan; Barbier, Antoine; Guichet, Christophe; Thomas, Olivier; Hustache, Stéphanie; Zozulya, Alexey V.; Thiaudière, Dominique
<x xml:space="preserve">Abstract</x> Structural anisotropy, for example texture, may govern important physical properties of thin film, such as electrical, magnetic and/or mechanical ones. Texture (orientation information) is typically observed and quantified by the measurement of so‐called pole figures. An optimized experimental approach implemented at the DiffAbs beamline (Synchrotron SOLEIL) is presented here. Using an X‐ray pixel area detector and synchrotron radiation sources, a complete pole figure (with resolutions adapted for metallic textured thin films, typically of the order of a few degrees) can be measured in time intervals as short as one minute. The necessary corrections enabling complete pole figure retrieval from the experimental data using this optimized approach are provided and discussed. A gain in measuring time by up to two orders of magnitude is found with respect to the use of a point detector (classical approach) under the same experimental conditions. Data measured using these two approaches are shown, compared and discussed.